2014
DOI: 10.2478/pjvs-2014-0008
|View full text |Cite
|
Sign up to set email alerts
|

Alternative for improving gut microbiota: use of Jerusalem artichoke and probiotics in diet of weaned piglets

Abstract: The aim of the study was to determine the effect of Jerusalem artichoke and probiotics on defence activity of intestinal cells of weaning pigs. One hundred eighty piglets (7 weeks old) were fed with basal feed supplemented with Jerusalem artichoke, Lactobacillus reuteri and Pediococcus pentosaceus. After 5 weeks, the piglets were slaughtered and the gastrointestinal contents and intestine samples were taken for analysis. Results demonstrated that in pigs fed basal diet with both probiotics and Jerusalem artich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
1
4
1
Order By: Relevance
“…The most prominent change attributable to the presence of L. reuteri was the reduced abundance of Enterobacteriaceae . This result conforms to prior reports obtained with diverse probiotic cultures (De Angelis et al, 2007 ; Konstantinov et al, 2008 ; Bednorz et al, 2013 ; Valdovska et al, 2014 ) and indicates that successful competition with Enterobacteriaceae is not a specific property of L. reuteri . Remarkably, this study also demonstrated that the abundance of several members of the Firmicutes and Bacteroidetes was influenced by L. reuteri .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The most prominent change attributable to the presence of L. reuteri was the reduced abundance of Enterobacteriaceae . This result conforms to prior reports obtained with diverse probiotic cultures (De Angelis et al, 2007 ; Konstantinov et al, 2008 ; Bednorz et al, 2013 ; Valdovska et al, 2014 ) and indicates that successful competition with Enterobacteriaceae is not a specific property of L. reuteri . Remarkably, this study also demonstrated that the abundance of several members of the Firmicutes and Bacteroidetes was influenced by L. reuteri .…”
Section: Discussionsupporting
confidence: 93%
“…Levan and reuteran are not digested by pancreatic digestive enzymes and selectively fermented by hindgut microbiota (Korakli et al, 2002 ; van Bueren et al, 2015 ). However, the exopolysaccharides levels in the feed used in this study, 1–3 g/kg feed (Yang et al, 2015 ), are low when compared to other studies reporting prebiotic intervention (Valdovska et al, 2014 ). Fermented feed containing reuteran, however, specifically reduced the abundance of enterotoxigenic E. coli (ETEC) in weanling piglets (Yang et al, 2015 ).…”
Section: Discussioncontrasting
confidence: 57%
“…microbiota in the caecal, colonic and rectal digesta. Valdovska et al [45] investigated the effect of TPB and probiotics on the gut microbiota of weaning pigs. Animals were fed for five weeks on an experimental diet supplemented with TPB and two probiotics (Lactobacillus reuteri and Pediococcus pentosaceus) in different doses.…”
Section: Tpb Studies In Animal Experimentsmentioning
confidence: 99%
“…The average degree of polymerisation also depends on the variety and ranges from 8 to 15 (Kocsis et al 2007;Matías et al 2011). Jerusalem artichoke may affect short chain fatty acids (SCFA) concentration in the pig manure and modulate microbiota composition in the large intestine (Farnworth et al 1995;Vhile et al 2012;Valdovska et al 2014) but its prebiotic potential is not well recognised. Therefore, the aim of the present study was to determine the effects of dried Jerusalem artichoke (DJA) tuber on microbial ecology and immune status of the large intestine of young pigs and to compare it with inulin extracted from chicory root.…”
Section: Introductionmentioning
confidence: 99%